ORGANOLEPTIC QUALITY CHARACTERISTICS OF GOLD FISH (Cyprinus carpio) WITH DIFFERENT PRESTO COOKING TIMES - Michael, Michael; Desmelati, Desmelati; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT` This study aims to determine the effect of different pressure cooker on the quality characteristics of shredded carp (Cyprinus carpio). The research method used was experiment by making carp shredded with different pressure cooking times. The design used was a non-factorial completely randomized design (CRD) with different presto cooking times, consisting of L0 (steamed carp for 30 minutes), L1 (carp press for 30 minutes), L2 (carp pressure for 45 minutes). ), L3 (goldfish pressure with a time of 60 minutes). Parameter analysis is organoleptic test (taste, texture, color, aroma). The results of the organoletic assessment analysis showed that the shredded carp with different pressure cooking times showed that the taste, color and texture, and aroma gave the highest value to the 60 minute pressure cooking time treatment, rather than the 30 minute and 45 minute pressure cooker treatment. Different presto cooking time affects the quality of shredded carp. Shredded carp with different presto cooking time of 60 minutes is produced shredded with a characteristic taste of shredded carp, the spices are strong, the color of the brown thorn shreds is no longer visible, the aroma is very fragrant without a fishy smell, the texture is crunchy, slightly oily and soft.Keywords: characteristic, , oganoleptic test, presto, floss